A relação entre currículo e educação integral em tempo integral: um estudo a partir da configuração curricular do Programa Mais Educação - RIBEIRO, Madison Rocha (Universidade Federal do Pará, 2017)
The thesis in question discusses the relationship between the curriculum configuration of the More Education Program and the perspective of full-time integral education adopted in this program by the Brazilian government. For this, it analyzes the curriculum prescribed in the More Education Program, in order to show the relationship between this curricular structure and the conception / purposes of the full-time integral education perspective expressed by the program. The research was based on the principles of the qualitative research approach, using documentary research as an operational method and content analysis as a technique for organizing and understanding documentary messages. The discussion of the object of investigation was based on the theoretical production of the field of curriculum and integral full-time education, which, together with the empirical corpus of research, constituted by six documents of the More Education Program, made it possible to construct the arguments in favor of Thesis defended. The analysis of the curricular prescriptions and the conception / purposes of full-time integral education showed the correspondence between the curricular configuration and the perspective of integral education prescribed in the PME. Based on this result, we develop and confirm the thesis that due to the conception of integral education, understood by the binomial formation and integral protection, as well as by its aims: reduction of educational inequalities and improvement of learning, Curricular configuration favoring the development of this conception / purposes of integral education, thus justifying the creation of thematic macro fields and the extension of school time, factors that can cause significant changes in the historical role of the public school, since this, besides developing a role Scientific educator, will also develop a protective role among the most vulnerable socially. In this sense, the thesis reaffirms the conception that the curriculum is a sociocultural and historical artifact, bearer of interests, beliefs and ideologies, capable of forming personal and social identities.